Potential role of chitinase‐3‐like protein 1 (CHI3L1/YKL‐40) in neurodegeneration and Alzheimer's disease. Issue 1 (2nd March 2022) - Connolly, Kevin; Lehoux, Mikael; O'Rourke, Ryan; Assetta, Benedetta; Erdemir, Guzide Ayse; Elias, Jack A; Lee, Chun Geun; Huang, Yu‐Wen Alvin
Abstract: Chitinase‐3‐like protein 1 (CHI3L1/YKL‐40) has long been known as a biomarker for early detection of neuroinflammation and disease diagnosis of Alzheimer's disease (AD). In the brain, CHI3L1 is primarily provided by astrocytes and heralds the reactive, neurotoxic state triggered by inflammation and other stress signals. However, how CHI3L1 acts in neuroinflammation or how it contributes to AD and relevant neurodegenerative conditions remains unknown. In peripheral tissues, our group and others have uncovered that CHI3L1 is a master regulator for a wide range of injury and repair events, including the innate immunity pathway that resembles the neuroinflammation process governed by microglia and astrocytes. Based on assessment of current knowledge regarding CHI3L1 biology, we hypothesize that CHI3L1 functions as a signaling molecule mediating distinct neuroinflammatory responses in brain cells and misfunctions to precipitate neurodegeneration. We also recommend future research directions to validate such assertions for better understanding of disease mechanisms.